Characteristics of the Microbial Community in the Production of Chinese Rice-Flavor Baijiu and Comparisons With the Microflora of Other Flavors of Baijiu - Hu, Yuanliang; Lei, Xinyi; Zhang, Xiaomin; Guan, Tongwei; Wang, Luyao; Zhang, Zongjie; Yu, Xiang; Tu, Junming; Peng, Nan; Liang, Yunxiang; Zhao, Shumiao (Frontiers in Microbiology, 2021)
Rice-flavor baijiu is one of the four basic flavor types of Chinese baijiu. Microbial composition plays a key role in the classification of baijiu flavor types and the formation of flavor substances. In this study, we used high-throughput sequencing technology to study the changes of microbial community in the production of rice-flavor baijiu, and compared the microbial community characteristics during production of rice-, light-, and strong-flavor baijiu. The results showed that the species diversity of bacteria was much higher than that of fungi during the brewing of rice-flavor baijiu. The bacterial diversity index first increased and then decreased, while the diversity of fungi showed an increasing trend. A variety of major microorganisms came from the environment and raw rice materials; the core bacteria were Lactobacillus, Weissella, Pediococcus, Lactococcus, Acetobacter, etc., among which Lactobacillus was dominant (62.88–99.23%). The core fungi were Saccharomyces (7.06–83.50%) and Rhizopus (15.21–90.89%). Temperature and total acid content were the main physicochemical factors affecting the microbial composition. Non-metric multidimensional scaling analysis showed that during the fermentation of rice-, light-, and strong-flavor baijiu, their microbial communities formed their own distinct systems, with considerable differences among different flavor types. Compared with the other two flavor types of baijiu, in the brewing process of rice-flavor baijiu, microbial species were fewer and dominant microorganisms were prominent, which may be the main reason for the small variety of flavor substances in rice-flavor baijiu. This study provides a theoretical basis for the production of rice-flavor baijiu, and lays a foundation for studying the link between baijiu flavor formation and microorganisms.